Evaluation of the polymorphism in the Toll-like receptor 4 (TLR4) genes of tympanosclerosis patients - Alpay, Hayrettin Cengiz; Etem, Ebru Onalan; Kaygusuz, Irfan; Yuce, Hueseyin; Karlidag, Turgut; Keles, Erol; Yalcin, Sinasi (Elsevier Sci Ltd, 2010)
Objective: Although eardrum perforations which endure etiopathogenesis for a long-time and middle ear infections are proposed for causing the tympanosclerosis (TS), tympanosclerosis emerges in some chronic otitis media (COM), some of them do not appear although a continuing COM and enduring perforation last. In this study, the effect of the molecular reasons which display genetic differences in TS formation is evaluated: our aim is to determine the Asp299Gly polymorphism frequencies in the TLR4 gene of patients with TS who have COM, and patients who do not. Materials and methods: Patients who have undergone COM surgery, were divided into two groups of 50 persons who were selected in accordance with the fact, whether they had TS in their middle car cavity or not during operation. 100 healthy persons who had similar demographic data, were evaluated as the control group. The DNA isolation was executed by using standard methods with peripheric blood specimen of the diseased group and control group. The Restriction Fragment Length Polymorphism method was used in determining the Asp299Gly allel in the TLR4 gene. Items of 249 bc for the wild tip (Asp) post-restriction enzyme segment wild tip (Asp) allel, and 23 bc and 196 bc post-restriction enzyme segment polymorphic allel (Gly) were obtained. Results: TLR4 Asp299Gly polymorphism (10%) was asserted in a total of five specimens in the diseased group with TS. TLR4 Asp299Gly polymorphism was found positive in only one (2%) of the 50 phenomenons in the group without TS. TLR4 Asp299Gly polymorphism was found positive in six (6%) of the 100 phenomenons in the control group. The positive polymorphism in phenomenons with TS was significant in accordance with statistics, when compared with the group without TS (p < 0.05). However, although the polymorphism rates were higher than the rates of the control group, it was not statistically significant (p > 0.05). Conclusion: TS may not appear in many patients who had undergone middle ear infection, and had perforation for many years. The polymorphism in arteriosclerosis in the TLR4 gene which caused the inflammatory cytokines oscillation recognize the bacterial LPS, was also accused. It is engrossing to find out from the results of our study on a restricted number of patients, and on only one gene, that molecular reasons which display genetic differences can also be effective in forming TS. Serial researches of greater dimensions are required. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Tympanosclerosis; TLR4 gene polymorphism